Recent advances in capillary electrophoresis of peptides - Kasicka, V (Electrophoresis, 2001)
The article gives a comprehensive review on the recent developments in the applications of high-performance capillary electromigration methods, including zone electrophoresis, isotachophoresis, isoelectric focusing, affinity electrophoresis, electrokinetic chromatography and electrochromatography, to analysis, preparation and physicochemical characterization of peptides. The article presents new approaches to the theoretical description and experimental verification of electromigration behavior of peptides, and covers the methodological aspects of capillary electroseparations of peptides, such as strategy and rules for the rational selection of separation mode and experimental conditions, sample treatment, suppression of peptide adsorption to the inner capillary wall, new developments in individual separation modes and new designs of detection systems. Several types of applications of capillary electromigration methods to peptide analysis are presented: conventional qualitative and quantitative analysis for determination of purity, determination in biomatrices, monitoring of physical and chemical changes and enzymatic conversions, amino acid and sequence analysis and peptide mapping of proteins. Some examples of micropreparative peptide separations are given and capabilities of capillary electromigration techniques to provide important physicochemical characteristics of peptides are demonstrated.
Keywords: Peptides; Electrophoresis, Capillary; elektroforéza kapilární; peptidy